2017
DOI: 10.1002/elsc.201700054
|View full text |Cite
|
Sign up to set email alerts
|

An improved high cell density cultivation—iHCDC—strategy for leucine auxotrophic Escherichia coli K12 ER2507

Abstract: An improved high cell density cultivation-iHCDC-strategy for leucine auxotrophic Escherichia coli K12 ER2507Fed-batch processes are commonly used tools in high cell density cultivation of Escherichia coli. However, the setup of a fed-batch process can be challenging, especially when working with genetically modified strains. This work deals with the design of a specific strategy for the leucine auxotrophic E. coli strain K12 ER2507 that is of interest for arabinose-inducible gene expression systems due to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Use of defined media is, however, not without its own pitfalls, and requires medium optimization and tweaking of feeding strategies in high-density cultivations. As an example, Beckmann et al 38 reported Leucine was inhibitory to leucine-auxotrophic Escherichia coli K12 ER2507 even at a concentration of 0.3 g L -1 . This effect could be overcome by optimizing the feeding strategy and medium composition.…”
Section: Cell Growth and Medium Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of defined media is, however, not without its own pitfalls, and requires medium optimization and tweaking of feeding strategies in high-density cultivations. As an example, Beckmann et al 38 reported Leucine was inhibitory to leucine-auxotrophic Escherichia coli K12 ER2507 even at a concentration of 0.3 g L -1 . This effect could be overcome by optimizing the feeding strategy and medium composition.…”
Section: Cell Growth and Medium Optimizationmentioning
confidence: 99%
“…While early approaches were trial and error processes, statistical techniques such as Response Surface Methodology (RSM) or factorial design can provide a more organized avenue for the Design of Experiments (DOE). Beckmann et al 38 applied full factorial design of experiments to optimize the concentration of glucose and leucine in the feed medium and achieved a cell density of 97 g L -1 for the leucine auxotrophic E. coli strain K12 ER2507. Subramaniam et al [48][49][50] developed a mi nimal medium by replacing costly yeast extract with vitamins such as biotin, calcium pantothenol and inositol.…”
Section: Cell Growth and Medium Optimizationmentioning
confidence: 99%
“…Most HCDC were designed only as the fed-batch technique and researched to the optimization of substrate feeding strategies to eliminate the problems of using too high concentration of substrate especially for glucose. Glucose or sucrose at a very high concentration enhances the biosynthesis of growth inhibitory by-products, i.e., acetate in bacteria and ethanol in yeasts due to the Crabtree effect [3,6]. The HCDC technique development often studies the optimum conditions of two main factors, i.e., media and cultivation technique, such as substrate feeding strategies.…”
Section: Introductionmentioning
confidence: 99%
“…It is a representative model microorganism of bacteria due to its holds several advantages, e.g., having more data both in genetics and culture conditions from long time investigations, well-explored characteristics, fast growth (doubling time of 15-20 min) on chemically defined media, cost effectiveness and scalability [6,13].…”
Section: Introductionmentioning
confidence: 99%